REINVIGORATING CLASSICAL ISLAMIC LITERACY THROUGH THE ALFASIH METHOD: A COMMUNITY-BASED SERVICE-LEARNING PROGRAM - Shulhan Shulhan (InEJ: Indonesian Engagement Journal, 2026)
Literacy in classical Islamic texts, as part of the classical Islamic literary tradition, is a crucial foundation of Islamic education in Indonesia. However, the ability to read and understand Arabic texts without vowel marks independently remains a challenge for many students. This community service activity aims to analyze the integration of service-learning with the Al-Fasih method in revitalizing classical Islamic text literacy among community-based learners. The program was implemented at the Ar-Rasyid Mosque in Duko Village, Rubaru Subdistrict, Sumenep Regency, involving 10 students from elementary and junior high school levels over an 18-month period through regular morning sessions following the congregational dawn prayer. This activity employed a qualitative approach based on Participatory Action Research, utilizing data collection techniques such as participatory observation, reflective journals, and interviews with students and parents. The results of the activity indicate that the integration of service-learning with the Alfasih method is capable of enhancing students’ ability to identify grammatical structures, comprehend meaning, and interpret classical texts, such as Safinatun Najah, Al-Ajurumiyyah, and Fath al-Qarib. Additionally, this program fosters intellectual independence, academic responsibility, and strengthens the sustainability of learning through community engagement. Thus, the integration of service-learning and the Alfasih method can serve as an innovative pedagogical model for strengthening classical Islamic text literacy within a community-based learning environment.